Numerical Visualization of Rudder Inflow as Effect of Increasing Angle of Attack - , Najmi S.M.; Priyanto, A; Yasser, M; Maimun, A A. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
This paper presents a study to examine the characteristics of the rudder inflow (propeller slipstream) using FLUENT v.6 visualization technique. The rotating propeller of 5 blades and semi-spade rudder were set in a uniform flow condition. The rudder distorts the angle-of-attack (AoA) or incident angle to the leading edge of the rudder blade. Time-averaged pressure and velocity field are proposed to analyze the AoA and show similar AoA values of 0°–7° at the region on rudder. However, it increases to 20° by those effects as the inflow comes to the rudder. From the AoA analysis the similar flow pattern is found to be about 7° in terms of the rudder angle. Cautious access is additionally necessary to introduce a reasonable safety against those inflow phenomena that would significantly influence the durability of the rudder.